2010
DOI: 10.1007/s00702-010-0386-7
|View full text |Cite
|
Sign up to set email alerts
|

Negative association between plasma cortisol levels and aggression in a high-risk community sample of adolescents

Abstract: In this study, the association of aggressive behavior and personality traits with plasma cortisol levels was investigated in a high-risk community sample of adolescents. Plasma cortisol levels were collected in 245 fifteen-year-olds (118 males, 127 females) from an epidemiological cohort study of children at risk for psychopathology. Additionally, measures of reactive and proactive aggression, externalizing behavior and callous-unemotional together with impulsive personality features were assessed. Both subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…Other studies have also found no such link in women11, and, overall, the effect seems to be more consistent in children than in older subjects59. The pre-post scan decrease in C levels could have been partly driven by scanner-induced drowsiness or by natural circadian variation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies have also found no such link in women11, and, overall, the effect seems to be more consistent in children than in older subjects59. The pre-post scan decrease in C levels could have been partly driven by scanner-induced drowsiness or by natural circadian variation.…”
Section: Discussionmentioning
confidence: 86%
“…Both hormones are considered to have a mutually opposing action678, and this divide is also apparent in human social behavior: T generally favors approach and aggression, while C leads to fear and avoidance910. This notion is supported by numerous findings in correlational11121314 and experimental settings151617, though not all evidence agrees. For instance, some studies in women have linked high, rather than low C concentrations with aggression1819, and high T with prosocial behavior202122.…”
mentioning
confidence: 96%
“…van Bokhoven et al, 2005), other studies find a negative association (e.g. Poustka et al, 2010), and yet others find no association (e.g. Alink et al, 2008).…”
Section: Basal Hormonesmentioning
confidence: 94%
“…Indeed, a large meta-analytic study reported that externalizing behavior is primarily related to dysregulated basal cortisol levels and shows no consistent relationship to HPA-axis reactivity (Alink et al, 2008). Third, In contrast to antisocial, aggressive, and impulsive behaviors convergent with factor 2 and secondary psychopathy more specifically, primary psychopathy has been consistently related to attenuated phasic HPA-axis reactivity to experimentally induced social stress (i.e., public speaking task) or physical stress (i.e., cannulation), but shows no consistent associations with basal levels (Cima et al, 2008;Dolan, Anderson, & Deakin, 2001;Feilhauer et al, 2013;Glenn, 2011b;Glenn et al, 2011;Loney et al, 2006;O'Leary, Taylor, & Eckel, 2010;Poustka et al, 2010;Stadler et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…CLARIFYING THE HETEROGENEITY IN PSYCHOPATHIC SAMPLES 55 Platje et al, 2013;Poustka et al, 2010;Van Goozen et al, 1998;Vanyukov et al, 1993;Windle, 1994), although some found higher levels of basal activity in conduct disordered and psychopathic adolescents (Van Bokhoven et al, 2005;Welker et al, 2014). Second, reactive aggression, conduct disorder, and antisocial behavior have been related to increased laboratory induced phasic HPA-axis reactivity (i.e., social stress task, social conflict situation, frustration induction, administration of exogenous cortisol), especially in females (Böhnke, Bertsch, Kruk, Richter, & Naumann, 2010;Kobak et al, 2009;LopezDuran, Olson, Hajal, Felt, & Vazquez, 2009;McBurnett et al, 2005;Susman et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%